EFEKTIVITAS MEDIA KOMIK MUHAMMAD AL-FATIH DALAM MENINGKATKAN KARAKTER RELIGIUS PESERTA DIDIK SDN 22 KOTA PAREPARE - Adhisti Adinda Putri; Ahdar; Abdul Halik; Mahsyar; Abdullah Thahir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine and analyze the effectiveness of using the Muhammad Al-Fatih comic media in improving the religious character of students at SDN 22 Parepare City. The research seeks to map the initial condition of students’ religious character before the treatment was administered, measure the changes that occurred after the use of comic media, and determine the level of effectiveness of the media through the acquisition of improvement scores (N-Gain Score). The main focus of this study is to provide an innovative solution in Islamic Religious Education (PAI) learning through visual media that is appropriate for the developmental stage of elementary school students. The research method employed was quantitative with a Pre-Experimental design of the One Group Pretest–Posttest type. The research sample consisted of 19 students selected using a purposive sampling technique. The data collection instrument was a religious character questionnaire consisting of 37 validated statement items. The data analysis techniques included descriptive statistical analysis and inferential analysis using the Wilcoxon Signed Rank Test and the N-Gain Score test. The implications of this research indicate that comic media effectively reduces students’ boredom in learning Islamic Religious Education and facilitates the internalization of abstract religious values into more concrete concepts for elementary school students. The use of inspirational figures such as Muhammad Al-Fatih provides a real model of exemplary behavior that can enhance students’ motivation and character development. These findings support the concept that the crystallization of religious character during the concrete operational stage is more optimally achieved through innovative visual media compared to conventional teaching methods.